Perlindungan Hukum bagi para pihak dalam Penerbitan Letter of Credit - Puspitorini, Lucky; Prasetyawati, Endang (CV. Era Digital Nusantara, 2025)
The Letter of Credit (L/C) is a crucial instrument in international trade, providing payment assurance for exporters and certainty for importers. However, its issuance process involves several legal risks that require specific attention. This research aims to examine the available forms of legal protection, the roles and responsibilities of banks in L/C issuance, and effective dispute resolution mechanisms. A normative juridical approach was employed for this study. Findings indicate a lack of dedicated national regulations specifically governing L/Cs. This regulatory gap creates a legal vacuum with the potential for disputes. Therefore, harmonization between the Uniform Customs and Practice for Documentary Credits (UCP 600) and national regulations is essential. This can be achieved through the adoption and ratification of specific L/C rules, either as government regulations or Bank Indonesia regulations. Such efforts are vital to ensure legal certainty for all parties involved. Furthermore, challenges in implementation and varying legal interpretations across different jurisdictions underscore the urgent need for legal reform. This research thus recommends policy reformulation and enhanced understanding of the legal risks associated with L/C issuance.